Geopolitics and the political right: lessons from Germany - Klinke, I (Oxford University Press, 2018)
In recent years, the Anglo-American media landscape has pondered over an old problem: that of German hegemony in Europe. At the heart of this debate lies the question of geopolitics. Is Germany, deliberately or by accident, a regional hegemon, and do its political elites seek to reorganize Berlin's neighbours into a pan-European architecture that prioritizes Germany's national interest? This question is not as straightforward as it may sound, not least because geopolitical thought was long a taboo in Germany, due to its influence on the formulation of National Socialist ideology in the 1920s. This article thus seeks to answer this question by focusing not on the often sanitized statements of political leaders but on the ideas of think-tankers, journalists, political advisers and public intellectuals, many of whom have had a significant influence on the formulation of German foreign policy. The article argues that, while geopolitical ideas were long confined to the right-wing margins of the political spectrum, they are now much more prevalent in the political mainstream. As Germany's relations with the United States and Russia have gradually soured, this new German geopolitics has once again become preoccupied by the notion of Germany as a central power.